Газові турбіни в децентралізованій енергетиці України - Khalatov, Artem; Borisov, Igor; Dashevckyy, Yuriy; Kobzar, Sergii (General Energy Institute of the National Academy of Sciences of Ukraine, 2026)
The article discusses the current state of application of gas turbine power plants for decentralized generation. The main types and thermodynamic cycles of the plants, their main advantages and disadvantages are analyzed, and a comparison with reciprocating gas turbines was made. Gas turbine power plants have a higher potential for heat generation in the combined cycle because they have a higher exhaust gas temperature. Some promising schemes of gas turbine plants that can be implemented in the future are listed. Data on the main manufacturers of gas turbine equipment, technical characteristics and specific cost of models available on the world market are presented. At present, a wide range of models of stationary and mobile gas turbine power plants of medium and low capacity of simple and combined (electricity and heat production and combined cycle plants) cycles are offered, which are intended specifically for decentralized generation. The efficiency of simple cycle power plants depends on the capacity and is 26-40 %, and the overall efficiency of CHP plants is 85-90%. The efficiency of medium-capacity co-generation plants is 50-55 %. In recent years the mobile equipment is developing intensively, which allow for quick installation and connection to the consumer: after connection, the power plant reaches full capacity within a short time - about 5 minutes. The environmental characteristics of gas turbine power plants meet modern requirements, NOx emissions do not exceed 25 ppm and for microturbines – 10 ppm. The role of gas turbine power plants in microgrids is considered. Microgrids can integrate various energy sources, both renewable (solar, wind, fuel cells) and conventional (gas turbine, diesel, gas piston), with the gas turbine being a key part of the microgrid that controls load, frequency, and voltage. When the energy supply from renewable sources decreases, the turbine compensates for all interruptions and ensures stable operation of the microgrid.